2003
DOI: 10.1897/02-255
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of cadmium, endosulfan, and atrazine in adrenal steroidogenic cells of two amphibian species, Xenopus laevis and Rana catesbeiana

Abstract: The effects of cadmium, endosulfan, and atrazine on corticosterone secretion and viability of adrenal cells of African clawed frog (Xenopus laevis) and bullfrog (Rana catesbeiana) were assessed in vitro using a new bioassay. The bioassay relies on stimulation with adrenocorticotropic hormone (ACTH), the endogenous secretagogue for corticosterone secretion, and with dibutyryl cyclic adenosine monophosphate (dbcAMP), an analogue of cAMP, to pinpoint the site of action of the xenobiotics within the steroidogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 34 publications
1
21
0
1
Order By: Relevance
“…Several pesticides may interfere with sexual hormones through direct action on receptors but also through indirect non-receptorial mechanisms (e.g. organochlorines: for review, see [99,113]; triazines: for review, see [114][115][116][117][118][119][120][121][122][123]; for 2,4-D: [124][125][126]. For other pesticides, it is reported that mutagenicity and alterations of other cellular processes including protein metabolism and cell proliferation may contribute to their clastogenic and tumorigenic activity (chloroacetanilides: [127]; halogenated hydrocarbon nematocide-DBCP: [128][129][130][131][132].…”
Section: Methodological Aspects Of the Present Meta-analysismentioning
confidence: 99%
“…Several pesticides may interfere with sexual hormones through direct action on receptors but also through indirect non-receptorial mechanisms (e.g. organochlorines: for review, see [99,113]; triazines: for review, see [114][115][116][117][118][119][120][121][122][123]; for 2,4-D: [124][125][126]. For other pesticides, it is reported that mutagenicity and alterations of other cellular processes including protein metabolism and cell proliferation may contribute to their clastogenic and tumorigenic activity (chloroacetanilides: [127]; halogenated hydrocarbon nematocide-DBCP: [128][129][130][131][132].…”
Section: Methodological Aspects Of the Present Meta-analysismentioning
confidence: 99%
“…They were collected using hand nets to prevent injury to animals during capture since they are active animals. Acclimation to laboratory conditions was done for two weeks prior to experiments (Goulet and Hontella, 2003) in plastic tanks measuring 49 cm in length x 29 cm in width x 24 cm in height with dechlorinated tap water (2 litres at a slant). The frogs were fed ad libitum daily with termites.…”
Section: Methodsmentioning
confidence: 99%
“…Unhatched embryos seem to be less sensitive to xenobiotic chemicals in the laboratory, as numerous experiments have resulted in delayed mortalities in jellied embryos when compared with non-jellied embryos [1,12,21,[24][25][26]. This is likely due to slower water uptake and lower clearance rate in the case of the jellied embryos [22,23].…”
Section: Effects Of Three Insecticides On Amphibian Tadpolesmentioning
confidence: 99%